PRESSURE-INDUCED HYDRATION IN ZEOLITE TETRANATROLITE - Lee Y.; Vogt T.; Hriljac J.A.; Parise J.B. (My University, 2006)
The tetranatrolite-paranatrolite transformation has remained a key problem in understanding the paragenesis of zeolites in the natrolite family. It is accepted that when paranatrolite, approximate formula Na16-xCaxAl16+xSi24-x O80.24H2O, is removed from an aqueous environment and exposed to the atmosphere, it loses water and transforms to tetranatrolite, Na16-xCaxAl16+x Si24-xO80.nH2O (n ≤ 24). Here we show that this transformation is not only reversible, but that tetranatrolite exhibits two sequential pressure-induced hydrations leading first to paranatrolite and then to a superhydrated tetranatrolite above 0.2 and 3.0 GPa, respectively. We have previously reported similar behavior for the corresponding system with an ordered Si/Al distribution, i.e., natrolite itself, however the ordered version of paranatrolite exists over a much smaller pressure range. The pressure-induced transformations of natrolite and tetranatrolite thus further supports the supposition that paranatrolite is a distinct mineral species, with a pressure-stability field dependent upon composition.
Keywords: CRYSTAL STRUCTURE; HIGH PRESSURE; PARANATROLITE; PHASE TRANSITION; PRESSURE-INDUCED HYDRATION; SYNCHROTRON X-RAY POWDER DIFFRACTION; TETRANATROLITE